Stylistic Analysis of Ayat al-Kursi (QS. Al-Baqarah: 255): A Study of Stylistic Elements and Their Meanings: revisi artikel - Qurrotula'yun, Arsyi; Inats Najma Karim; Mochammad Fathur Rozak (Proceedings of International Conference on Islamic Civilization and Humanities, 2025)
Ayat al-Kursi (QS. Al-Baqarah: 255) holds a central position in Qur'anic theological studies due to its comprehensive content regarding the omnipotence of Allah. This study examines the linguistic aspects of the verse through an Arabic stylistic approach by exploring rhetorical strategies and linguistic patterns that reinforce the message of monotheism (tawhid).Using a descriptive qualitative method, this research conducts a stylistic analysis that allows for the examination of elements such as metaphor, symbolism, and rhetoric. The findings show that Ayat al-Kursi contains a range of complex and profound stylistic features, which convey deep meanings about the power and majesty of Allah.Preliminary findings suggest that the stylistic elements used in Ayat al-Kursi play a crucial role in shaping its meaning and message. These findings support the thesis that the rhetorical power of Ayat al-Kursi does not lie in structural complexity, but in its transformative ability to shape awareness of monotheism through linguistic precision and semantic depth.